2022
DOI: 10.1097/j.jcrs.0000000000000746
|View full text |Cite
|
Sign up to set email alerts
|

One-year multicenter evaluation of a new hydrophobic acrylic intraocular lens with hydroxyethyl methacrylate in an automated preloaded delivery system

Abstract: The Clareon IOL showed excellent clinical outcomes with no glistenings, and AutonoMe received high ratings on its usability and performance by surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“… 4 Similarly, in a 1-year study in 384 patients in Japan, the Clareon IOL demonstrated good visual acuity and low postoperative refractive error. At 12 months, 95% of eyes achieved BCDVA of 20/25 (~0.2 logMAR) or better, and refractive error in 90% of eyes was within 1.0 D. 6 A 4- to 6-week follow-up study that evaluated the Clareon AutonoMe system in 144 eyes in Germany also reported good visual acuity and low postoperative refractive error; in patients without ocular comorbidities, BCDVA improved from 0.27 to 0.03 logMAR. 15…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“… 4 Similarly, in a 1-year study in 384 patients in Japan, the Clareon IOL demonstrated good visual acuity and low postoperative refractive error. At 12 months, 95% of eyes achieved BCDVA of 20/25 (~0.2 logMAR) or better, and refractive error in 90% of eyes was within 1.0 D. 6 A 4- to 6-week follow-up study that evaluated the Clareon AutonoMe system in 144 eyes in Germany also reported good visual acuity and low postoperative refractive error; in patients without ocular comorbidities, BCDVA improved from 0.27 to 0.03 logMAR. 15…”
Section: Discussionmentioning
confidence: 95%
“…eyes was within 1.0 D. 6 A 4-to 6-week follow-up study that evaluated the Clareon AutonoMe system in 144 eyes in Germany also reported good visual acuity and low postoperative refractive error; in patients without ocular comorbidities, BCDVA improved from 0.27 to 0.03 logMAR. 15 The material and design of the Clareon IOL were aimed to reduce the risk of PCO and to achieve low levels of surface haze and glistenings.…”
mentioning
confidence: 87%
See 3 more Smart Citations